RETRACTED: A modified approach to professional learning communities in mathematics: Fostering teacher reflection around formative assessments of students’ thinking - Needs, Makayla; Bahr, Damon L.; McMillan, Brandon G.; Nixon, Ryan S.; Braden, Quinn H.; Royster, Rachel (Frontiers in Education, 2022)
A team of three third grade teachers utilized a modified approach to Professional Learning Communities (PLCs) based on principles and procedures that characterize Lesson Study to collaborate about their mathematics instruction. They gathered to design mathematical tasks and anticipate the thinking those tasks might elicit. Subsequent to facilitating lessons based on those tasks, they gathered again to compare the thinking they observed to the thinking they anticipated they would see, and to design additional tasks informed by their observations. This paper reports on an investigation conducted by one of the teachers who assumed the role of a native, participant researcher as she qualitatively studied the nature of the teachers’ reflections as they collaborated on five occasions. The six domains of “Mathematical Knowledge for Teaching” (MKT; Ball, Thames, & Phelps, 2008) were used as a conceptual framework for analysis, particularly in looking for connections the teachers were making between or among MKT domains. Our analysis revealed that the teachers learned to consistently engage in very complex thinking that involved interconnected webs representing multiple MKT domains. Furthermore, evidence suggests that the construction of these webs influenced changes in teacher perspectives on the nature of mathematics teaching and learning and produced an increased interest and ability in “making serious use of student thinking,” (Ball, 2001). Such an approach to conducting PLCs appears to possess some potential as a grass roots means of promoting mathematics education reform.